Proceedings of the Sixth Padang International Conference on Economics Education, Economics, Business and Management, Accounting 2021
DOI: 10.2991/aebmr.k.210616.013
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Gender and Machiavellianism on Tax Evasion (A Study on Accounting Students)

Abstract: This study aims to examine the influence of gender and Machiavellianism on tax evasion. This research is a causative research focusing on the context of accounting students. The data for this study were collected by using electronic survey distributed to 151 accounting students at Faculty of Economics, Universitas Negeri Padang. Multiple regression was used to analyze the data. The findings of this study show that gender has significant influence on tax evasion among accounting students. In particular, men ten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In his research, Fisher stated that gender is a psychosocial factor that can influence a person's success in influencing tax evasion (Fischer et al 1992). Research supports previous research stating that women tend to comply with taxes (Helmy et al 2021;Hogue et al 2013;Julianto 2013;Kastlunger et al 2010;Sommers 2003).…”
Section: Differences In Tax Evasion Behavior In Men and Womenmentioning
confidence: 54%
See 1 more Smart Citation
“…In his research, Fisher stated that gender is a psychosocial factor that can influence a person's success in influencing tax evasion (Fischer et al 1992). Research supports previous research stating that women tend to comply with taxes (Helmy et al 2021;Hogue et al 2013;Julianto 2013;Kastlunger et al 2010;Sommers 2003).…”
Section: Differences In Tax Evasion Behavior In Men and Womenmentioning
confidence: 54%
“…This research will later test accounting students for tax evasion, this is because students are considered capable of representing practitioners in decision making (Liyanarachchi and Milne 2005). According to Helmy et al, (2021), research that done By using students as an important subject, especially students with an undergraduate study program majoring in accounting will become someone who is directly involved as a business person who will play a role in carrying out and fulfilling all duties, responsibilities and tax obligations in the future. Apart from that, students will also make ethical decisions regarding their tax obligations.…”
Section: Introductionmentioning
confidence: 99%
“…Machiavellianism and the love of money are linked to unethical behavior, which has a negative impact on accounting students' perceptions of ethical behavior (Maggalatta & Adhariani, 2020). Helmy, Dwita, and Cheisviyanny (2021) found that tax evasion among accounting students to be significantly influenced by gender. Their study found females as more compliant and males as more prone to commit tax evasion; however, they found no link between Machiavellian behavior and tax evasion.…”
Section: Literature Reviewmentioning
confidence: 99%